Sisters of St. Dorothy: an answer? (1866-1910) - Irmã Diana Barbosa (Escola Superior de Educação de Paula Frassinetti, 2016)
Implantation of the Congregation of the Sisters of St.  Dorothy inPortugal. Initial difficulties. New answers. Paula Frassinetti visits the Sisters. Development of the Institute inPortugal. Foundations: 1875-1910. Development of theCollegeofQuelhas. The Religious Persecution of 1901. The Revolution of October 1910 and the expulsion. Dispersion. Keywords   Dorothy;Portugal; Education;  Expansion.